Coaching-Based Leadership Intervention Program: A Controlled Trial Study - Peláez Zuberbuhler, María Josefina; Salanova, Marisa; Martínez, Isabel M. (Frontiers in Psychology, 2020)
In spite of the potential benefits that coaching-based leadership interventions can bring to organizations, basic questions remain about their impact on developing coaching skills and increasing psychological capital, work engagement and in- and extra-role performance. In a controlled trial study, 41 executives and middle managers (25 in the experimental group and 16 in the waiting-list control group) from an automotive sector company in Spain received pre-assessment feedback, a coaching-based leadership group workshop, and three individual executive coaching sessions over a period of three months. The intervention program used a strengths-based approach and the RE-GROW model, and it was conducted by executive coaching psychologists external to the organization. Participants (N=41) and their supervisors (N=41) and employees (N=180) took part in a pre-post-follow up 360-degree assessment during the research period. Quantitative data were analyzed using Analyses of Variance with a 2 x 2 design, paired-samples t-tests, and univariate analyses between groups. Results indicated that the intervention program was successful in increasing the participants’ coaching-based leadership skills, psychological capital, work engagement, and in- and extra-role performance. Qualitative measures were also applied, and results from individual responses provided additional support for ed the study hypotheses. Regarding practical implications, the results suggest that the Coaching-based Leadership Intervention Program can be valuable as an applied positive intervention to help leaders develop coaching skills and enhance well-being and optimal functioning in organizations.